Réponses

2013-06-04T22:04:25+02:00

A = 2/5 +5/12 -1/15 = le dénominateur sera 60

A = 2/5 X 12/12 + 5/12 X 5/5 -1/15 X 4/4

A = 24/ 60 + 25/60 -4/60

A = 49/60 -4/60 = 45/60 = 9/12 = 3/4 Proposition N° 3

 

B= 8/25 divisé 16/75 = 8/25 X 75/16 = 600/400 = 6/4 = 3/2 Proposition N°2

 

C= (2x-5)² identité remarquable

C= 4x² -20 x +25              Proposition N°2

 

D= 49x² -25 = (7x-5)(7x+5)    Proposition N° 2

 

E= (x+3)(x-5) - (x-2)(x+3) 

E = (x² -5x +3x -15) - ( x² +3x -2x -6) 

E = (x² -2x -15) - (x² +x -6)

E = x² -2x -15 -x² -x +6

E = -3x -9  = -3(x+3)                        Proposition N° 3

 

-2 est solution de : (x-2)(2x+4)=0

x-2=0

x = 2

2x+4=0

2x = -4

x = -4/2 = -2    Proposition N°1

 

Exercice 2.

 

Développement et réduction

G = (5x-3)² + (+5x-3)(3x +2)

G = ( 25x² -30x +9) + ( 15x² +10x -9x -6)

G = 25x² -30x +9 +15x² +x -6

G = 40x² -29x +3

 

Factorisation

G = (5x -3)(5x-3) + (5x-3)(3x+2)

G = (5x-3) ( 5x-3 +3x +2)

G = (5x-3) (8x -1)

 

Equation

(5x-3)(8x-1) = 0

5x-3 = 0

5x = 3

x= 3/5

 

8x-1=0

8x=1

x= 1/8

3/5 et 1/8 sont les solutions de l'équation.

 

G pour x = -1

G = (5x-3)² + (+5x-3)(3x +2)

G = (5 X -1 -3)² +(+5X-1 -3)(3X-1 +2)

G = (-5 -3)²+ (-5 -3)(-3 +2)

G = (-8)² + +15 -10 +9 -6

G = + 64 +15 -10 +9 -6

G = +88 - 16

G= +72